(untitled) (Research, Society and Development, 2023)
Objective: to analyze, through the scientific literature, the main difficulties encountered by newly graduated nurses, who are not managers of intensive care units. Method: This is an Integrative Literature Review of a critical and retrospective nature, with primary data sources, using the combinations of the two following descriptors: "Nursing Students", "Nursing", "Intensive Care Units", "Management of Professional Practice ", "Professional Practice", "Labor Market" identified by means of two Health Sciences Descriptors, linked by the Boolean operator "or". Search in Latin American and Caribbean Literature in Health Sciences databases (LILACS), Nursing Database (BDENF), System for Analysis and Retrieval of Online Medical Literature (MEDLINE) and Scientific Electronic Library Online (SciELO). Inclusion criteria: articles available in full, published in the last 10 years. Results: 11 articles were selected and these emerged from two thematic categories: Need for professional qualification due to the complexity of managing care in the therapy unit the intensive care unit and the difficulty of managing new graduates in the intensive care unit. Final considerations: Faced with two different existing conflicts, it was possible to analyze that the newly graduated nurse in the intensive care unit needs to be constantly updated, promoting skills to develop strategies that alleviate the difficulties encountered.